2015
DOI: 10.1007/s10816-015-9254-y
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Behavioral Flexibility? An Integrative Macro-Scale Approach to Understanding the Middle Stone Age of Southern Africa

Abstract: The Middle Stone Age (MSA) of southern Africa represents a period during which anatomically modern humans adopted a series of diverse cultural innovations. Researchers generally attribute these behavioral changes to environmental, neurological, or demographic causes, but none of these alone offers a satisfactory explanation. Even as patterns at site level come into focus, large-scale trends in cultural expansions remain poorly understood. This paper presents different ways to view diachronic datasets from loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 141 publications
1
19
1
Order By: Relevance
“…When analyses are carried out at the technocomplex scale there is an untested assumption that all the changes in the multiple traits that characterize the technocomplex are coeval and influenced by the same processes. Some recent investigations have found no association between the appearance of new MSA technocomplexes and environment [95, 121123]. However, those studies did not test for an association between individual lithic assemblage traits and environmental change, and in that way their methodologies differ significantly from ours.…”
Section: Sample Selection and Methodscontrasting
confidence: 60%
See 3 more Smart Citations
“…When analyses are carried out at the technocomplex scale there is an untested assumption that all the changes in the multiple traits that characterize the technocomplex are coeval and influenced by the same processes. Some recent investigations have found no association between the appearance of new MSA technocomplexes and environment [95, 121123]. However, those studies did not test for an association between individual lithic assemblage traits and environmental change, and in that way their methodologies differ significantly from ours.…”
Section: Sample Selection and Methodscontrasting
confidence: 60%
“…The decision to choose silcrete over quartzite might not be explained solely by economic factors, which is a perspective in line with a recent study of MSA and LSA silcrete abundance [175], and hypotheses that link raw material selection to aspects of reciprocal exchange and symbolism [52, 53]. The traits not listed in Table 4 are also good candidates for understanding the meaning of continuity in material culture style across space in South Africa and for exploring the ideas that similarities were reinforced by contact and exchange among and between early modern human foragers [51, 92, 172, 176], that short-term temporal changes in technological behavior and differences between sites could reflect local socio-cultural historical trajectories [56, 118, 177], and that a holistic consideration of what drove MSA technological change will include a consideration of non-environmental factors [95, 119, 121, 123]. Further investigations of intra-MIS variability at PP5-6 will also contribute to better understanding the diversity of factors—environmental, economic, functional, and socio-cultural—that operate on finer-scales to influence technological behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The statistical tests demonstrated that Levallois technology involved the most rapid rate of phase changes and the highest hierarchical breadth throughout the sequences. This supports those that have emphasised the complexity of Levallois technology as well as the hypothesis that a major component of the Acheulean to Middle Palaeolithic transition was an increase in hierarchical behaviour and cognition (Ambrose 2001;Eren and Lycett 2012;Kandel et al 2016;Moore 2010;Schlanger 1996;Shipton et al 2013b;Wynn and Coolidge 2004;2010b).…”
Section: Discussionsupporting
confidence: 84%